Analyze The Contract of Broiler Partnership Farming System in the Province of South Sulawesi in Conjunction to the Law No. 5, 1999 Regarding Prohibition on Monopolistic and Unfair Business Competition - S. N. Sirajuddin; M. Aminawar; St. Rohani; V. S. Lestari; A. R. Siregar; T. Aryanto (Jurnal Ilmu dan Teknologi Peternakan, 2015)
This research aimed to analyze the contract of broiler partnership farming system in the Province of South Sulawesi in conjunction to the Law No. 5, 1999 regarding prohibition on monopolistic and unfair business competition. This research was carried out from August 2013 till October 2013 in Maros and Gowa Districts of South Sulawesi. All broiler farmers were treated as the population of the study and farmers having contract with any company in the region were taken as the samples giving total number of sample was 50 farmers. The results of study showed that the implementation of partnership was in line with the contract. However, there were some points of the contract which were not well implemented by both parties, such as the late harvest time and the late payment in which these did not comply with the Law No. 5, 1999.